2019
DOI: 10.3390/ijerph16224530
|View full text |Cite
|
Sign up to set email alerts
|

Progreso en Salud: Findings from Two Adapted Social Network HIV Risk Reduction Interventions for Latina Seasonal Workers

Abstract: Background: Miami-Dade County, where many Latina seasonal workers reside and work, has the highest incidence of the human immunodeficiency virus (HIV) in the US: a rate four times the national average. Despite this disproportionate risk for HIV, there are no HIV prevention interventions that aim to decrease HIV among Latina seasonal workers. Methods: The PROGRESO EN SALUD study compared the outcomes of two interventions adapted to include a social network component (VOICES and HEALTHY). Recruitment used a soci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…This commentary builds on lessons learned from our social network-based HIV prevention intervention called PROGRESO [ 14 , 15 ]. In this study, our team found that the vast majority of Latinx seasonal farmworkers live in fear due to the threat of deportation and discrimination [ 9 ].…”
Section: Social Network Approach As a Strategy To Overcome Challenges Of Pandemic Tracking Treatment And Acceptance Of Sars-cov-2 Testingmentioning
confidence: 99%
See 4 more Smart Citations
“…This commentary builds on lessons learned from our social network-based HIV prevention intervention called PROGRESO [ 14 , 15 ]. In this study, our team found that the vast majority of Latinx seasonal farmworkers live in fear due to the threat of deportation and discrimination [ 9 ].…”
Section: Social Network Approach As a Strategy To Overcome Challenges Of Pandemic Tracking Treatment And Acceptance Of Sars-cov-2 Testingmentioning
confidence: 99%
“…The lessons we have learned from PROGRESO could inform potential approaches for promoting SARS-CoV-2 testing, tracing, social isolation, treatment and vaccination [ 14 , 15 ]. Using community-based participatory research approaches, we identified a community partner located in a Latinx seasonal working community in South Florida to implement the study.…”
Section: Social Network Approach As a Strategy To Overcome Challenges Of Pandemic Tracking Treatment And Acceptance Of Sars-cov-2 Testingmentioning
confidence: 99%
See 3 more Smart Citations